2017
DOI: 10.3748/wjg.v23.i16.2891
|View full text |Cite
|
Sign up to set email alerts
|

Droplet digital PCR for quantification ofITGA6in a stool mRNA assay for the detection of colorectal cancers

Abstract: AIMTo investigate the use of droplet digital polymerase chain reaction (ddPCR) for detecting host mRNA markers in stools as a non-invasive test for colorectal cancer screening.METHODSddPCR and quantitative PCR were compared side by side for their performance in the detection of ITGA6 and ITGA6A transcripts in stool samples obtained from patients with various types of colorectal lesions (advanced adenomas and stage II-IV colorectal cancers) and control (patients displaying no pathological findings) using duplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
(66 reference statements)
2
14
0
Order By: Relevance
“…Indeed, ITGA6 levels were found to be increased in stool samples of AA and CRC at all stages while receiver operating characteristic (ROC) curves revealed that ITGA6 as a single marker can predict 75% of the AA and 81% of the CRC, with a 88% specificity [69]. Comparable results were also obtained using droplet digital PCR [70]. Interestingly, increases in stool ITGA6A levels were only found in samples from patients with CRC, consistent with previous observations in primary tumours [43,44].…”
Section: Screening Factorssupporting
confidence: 87%
“…Indeed, ITGA6 levels were found to be increased in stool samples of AA and CRC at all stages while receiver operating characteristic (ROC) curves revealed that ITGA6 as a single marker can predict 75% of the AA and 81% of the CRC, with a 88% specificity [69]. Comparable results were also obtained using droplet digital PCR [70]. Interestingly, increases in stool ITGA6A levels were only found in samples from patients with CRC, consistent with previous observations in primary tumours [43,44].…”
Section: Screening Factorssupporting
confidence: 87%
“…Given these advantages, it can be used to determine the expression and copy number variation analysis of the target gene [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a very recent study, ddPCR was also used to quantify an mRNA biomarker, ITGA6 , in stool from patients with CRC[ 17 ]. Tumor-derived nucleic acids present in stool samples come from the exfoliation of tumor cells of the intestinal mucosa and are a non-invasive, alternative source of genetic material for KRAS oncogene mutation screening in CRC patients[ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stool-derived DNA is a potential non-invasive alternative source of DNA for tumor genotyping in CRC due to the high rate of exfoliation of tumor cells into the bowel lumen[ 17 ]. Digital PCR was first described in 1999 by Vogelstein and Kinzler in a study aimed at identifying KRAS in DNA obtained from fecal samples of CRC patients[ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation